2007
DOI: 10.1037/0735-7044.121.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of sexual arousal in homosexual and heterosexual men.

Abstract: Men exhibit much higher levels of genital and subjective arousal to sexual stimuli containing their preferred sex than they do to stimuli containing only the nonpreferred sex. This study used event-related functional magnetic resonance imaging to investigate how this category-specific pattern would be reflected in the brains of homosexual (n = 11) and heterosexual (n = 11) men. Comparisons of activation to preferred sexual stimuli, nonpreferred sexual stimuli, and sports stimuli revealed large networks correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 65 publications
8
95
2
Order By: Relevance
“…(The brain regions that activate during sexual arousal have already been established by fMRI studies.) Studies using fMRI technology have already demonstrated that homosexual and heterosexual teleiophiles can be accurately differentiated according to brain activity during exposure to erotic photographs of adult men and women (e.g., Safron et al, 2007). It has not yet been investigated whether fMRI can differentiate accurately between pedohebephiles and teleiophiles.…”
Section: Laboratory Tests For Pedohebephiliamentioning
confidence: 97%
“…(The brain regions that activate during sexual arousal have already been established by fMRI studies.) Studies using fMRI technology have already demonstrated that homosexual and heterosexual teleiophiles can be accurately differentiated according to brain activity during exposure to erotic photographs of adult men and women (e.g., Safron et al, 2007). It has not yet been investigated whether fMRI can differentiate accurately between pedohebephiles and teleiophiles.…”
Section: Laboratory Tests For Pedohebephiliamentioning
confidence: 97%
“…Lippa (2011) assessed heterosexual men and women's sexual aversion ratings and found that the men's aversion ratings were more consistent than the women's aversion ratings (i.e., ''Having sexual relations with this person would be extremely unpleasant to me''). Safron, Barch, Bailey, Parrish, and Reber (2007) used fMRI scans to assess homosexual and heterosexual men's arousal in their brain. Safron et al did not find any region consistently activated to the non-preferred sexual stimuli, although they noted that they might not have assessed brain regions regulating aversion.…”
Section: What We Need To Knowmentioning
confidence: 99%
“…For example, erotic stimuli elicit neuronal activities in brain areas commonly associated with the human reward system (e.g., Ishai, 2007;Karama et al, 2002;Mouras et al, 2003;Ponseti et al, 2006;Redouté et al, 2000;Safron et al, 2007;Stoléru et al, 1999). Visual stimuli of sexually attractive targets may also trigger schematic processes (e.g., evaluative, comparative, or associative processes, episodic memories, fantasizing).…”
Section: Stimulus-specific Processesmentioning
confidence: 99%